Alat Pemintal Sabut Kelapa Berbasis Kecepatan - S Sefiyuchanna; Mukhamad Fauzi; Sri Jumini (Center for Intellectual Property and Technology Innovation, Universitas Sains Al-Qur'an, 2025)
The accumulation of coconut fiber waste and limited spinning technology causes the rope production process to remain slow and have low economic value for small business owners. This study aims to design a coconut fiber spinning tool based on speed control and analyze the effect of electrical power on the rope length and rotations per minute (RPM) produced. The research method uses an experimental approach with stages of tool design, assembly, testing, and performance evaluation gradually following the waterfall flow. Tests were carried out with power variations of 30 W, 35 W, 40 W, and 45 W at a constant spinning time of 60 seconds, then the RPM value and the resulting rope length were measured. The results showed a directly proportional relationship between power, RPM, and rope length. At 30 W power, the RPM was obtained at 32 with a rope length of 1.72 meters, while at 45 W power, the RPM increased to 72 and the rope length reached 2.94 meters. Increasing power increases the dynamo rotation speed and the effectiveness of the winding process, so that production capacity increases at the same time.